Question
upstudy study bank question image url

Find the derivative of the function \( T(x)=\tan \left(\frac{2 x+7}{3 x-1}\right) \)

Ask by Paul Rose. in the United States
Feb 27,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The derivative of \( T(x) = \tan\left(\frac{2x + 7}{3x - 1}\right) \) is \( T'(x) = -\frac{23 \sec^2\left(\frac{2x + 7}{3x - 1}\right)}{(3x - 1)^2} \).

Solution

To find the derivative of T(x) = tan((2x + 7) / (3x - 1)), we can use the chain rule. Step 1. Identify the inner function:   u(x) = (2x + 7) / (3x - 1). Step 2. Differentiate T(x):   Since T(x) = tan(u(x)), its derivative is:     T'(x) = sec²(u(x)) · u'(x). Step 3. Differentiate u(x) using the quotient rule:   The quotient rule states that if u(x) = N(x) / D(x), then     u'(x) = [D(x)·N'(x) - N(x)·D'(x)] / [D(x)]². Here,   N(x) = 2x + 7  and  D(x) = 3x - 1.   Thus, N'(x) = 2  and  D'(x) = 3. So,   u'(x) = [(3x - 1)(2) - (2x + 7)(3)] / (3x - 1)². Simplify the numerator:   (3x - 1)(2) = 6x - 2,   (2x + 7)(3) = 6x + 21,   Therefore, numerator = (6x - 2) - (6x + 21) = -23. Thus,   u'(x) = -23 / (3x - 1)². Step 4. Substitute u(x) and u'(x) into the chain rule:   T'(x) = sec²((2x + 7) / (3x - 1)) · (-23 / (3x - 1)²). Final Answer:   T'(x) = -23 sec²((2x + 7) / (3x - 1)) / (3x - 1)².

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To find the derivative of the function \( T(x) = \tan \left(\frac{2x + 7}{3x - 1}\right) \), we can use the chain rule and the quotient rule. 1. **Chain Rule**: The derivative of \( \tan(u) \) is \( \sec^2(u) \cdot u' \), where \( u = \frac{2x + 7}{3x - 1} \). 2. **Quotient Rule**: To find \( u' \), apply the quotient rule: if \( u = \frac{f(x)}{g(x)} \), then \( u' = \frac{f'g - fg'}{g^2} \). Here, \( f(x) = 2x + 7 \) and \( g(x) = 3x - 1 \). - \( f'(x) = 2 \) - \( g'(x) = 3 \) Now applying the quotient rule: \[ u' = \frac{(2)(3x - 1) - (2x + 7)(3)}{(3x - 1)^2} \] Simplifying this gives: \[ u' = \frac{6x - 2 - 6x - 21}{(3x - 1)^2} = \frac{-23}{(3x - 1)^2} \] 3. Now substituting \( u' \) back into the derivative of \( T(x) \): \[ T'(x) = \sec^2\left(\frac{2x + 7}{3x - 1}\right) \cdot \left( \frac{-23}{(3x - 1)^2} \right) \] Finally, you can express the derivative as: \[ T'(x) = -23 \cdot \frac{\sec^2\left(\frac{2x + 7}{3x - 1}\right)}{(3x - 1)^2} \] So the derivative of \( T(x) = \tan \left(\frac{2 x+7}{3 x-1}\right) \) is: \[ T'(x) = -23 \cdot \frac{\sec^2\left(\frac{2x + 7}{3x - 1}\right)}{(3x - 1)^2} \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy